Paucity And Multitude In The Holy Quran: Denotative Analysis Study - Al-Samarrai, Mohammed Fadhel Saleh (Al-Adab Journal, 2019)
This study examines the issue of paucity and multitude in the Holy Quran: a semantic analytical study. It deals with different patterns and multiple images to denote paucity and multitude in the Holy Quran. It addresses different cases of broken and sound plurals, singular and plural, masculine and feminine. The study reveals findings including that the word may have two types of broken plural; one of them is for paucity and the other one is for multitude. The meaning of paucity plural refers of the number ranging between three to ten; but if the number exceeds ten, it will be multitude plural. Paucity plural may refer to relative paucity. If the word has two plural forms, one of them is sound and the other is broken, then the sound will be for paucity and the broken plural will be for multitude. It is noteworthy that sound plural and paucity does not mean that the number should always be ranging between three to ten, as it could be so and could refer to that if the word has two plural forms one of them is sound and the other is broken; hence, the sound plural is less than the broken plural regardless of number. In addition, masculine may refer to paucity and feminine may refer to multitude.